2017
DOI: 10.1371/journal.pone.0173505
|View full text |Cite
|
Sign up to set email alerts
|

The mode and tempo of genome size evolution in the subgenus Sophophora

Abstract: Genome size varies widely across organisms, with no apparent tie to organismal complexity. While genome size is inherited, there is no established evolutionary model for this trait. Hypotheses have been postulated for the observed variation in genome sizes across species, most notably the effective population size hypothesis, the mutational equilibrium hypothesis, and the adaptive hypothesis. While much data has been collected on genome size, the above hypotheses have largely ignored impacts from phylogenetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 39 publications
(48 reference statements)
1
20
0
Order By: Relevance
“…Assembly quality varied greatly among the 15 genomes, with an average contig N50 of 4.4 Mb, a maximum of 16.6 Mb ( D. erecta ), and a minimum of 0.6 Mb ( D. bipectinata ). For each species, assembly resulted in genome sizes that were smaller than the expected genome size ( Bosco et al 2007 ; Gregory and Johnston 2008 ; Hjelmen and Johnston 2017 ), with repetitive sequence likely accounting for the lower values than expected. We also compared assembly statistics for each of our de novo assemblies to the published assembly of each species and found that in all cases our contig N50 values were higher than those of the published assemblies but lower than the scaffold N50 values (scaffold N50 is a measure similar to contig N50, in which half of the genome is contained in linked DNA segments, or scaffolds, larger than the value given) in all but three cases ( Table 3 ).…”
Section: Resultsmentioning
confidence: 91%
“…Assembly quality varied greatly among the 15 genomes, with an average contig N50 of 4.4 Mb, a maximum of 16.6 Mb ( D. erecta ), and a minimum of 0.6 Mb ( D. bipectinata ). For each species, assembly resulted in genome sizes that were smaller than the expected genome size ( Bosco et al 2007 ; Gregory and Johnston 2008 ; Hjelmen and Johnston 2017 ), with repetitive sequence likely accounting for the lower values than expected. We also compared assembly statistics for each of our de novo assemblies to the published assembly of each species and found that in all cases our contig N50 values were higher than those of the published assemblies but lower than the scaffold N50 values (scaffold N50 is a measure similar to contig N50, in which half of the genome is contained in linked DNA segments, or scaffolds, larger than the value given) in all but three cases ( Table 3 ).…”
Section: Resultsmentioning
confidence: 91%
“…While transposable elements are capable of substantially altering genome size and structure, the presence of indels also contributes to genome size and collinearity ( Petrov 2002 ; Gregory 2003 ; Vitte and Bennetzen 2006 ; Hjelmen and Johnston 2017 ; Kapusta et al 2017 ). Previous work in cotton suggests there exist small differences in rates between species with large and small genomes that contribute to overall genome size change ( Grover et al 2008a ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work that looks at genome size evolution in a phylogenetic context, finds various patterns for change (Arnqvist et al 2015; Jeffery et al 2016; Sessegolo et al 2016; Hjelmen and Johnston 2017; Lower et al 2017). Most of these have focused on widely-diverged species.…”
mentioning
confidence: 99%
“…Species in the genus Drosophila have been the subject of a wide variety of biological studies, including phylogenetics and genome size (Gregory and Johnston 2008; Van Der Linde and Houle 2008; Van Der Linde et al 2010; Hjelmen and Johnston 2017; Hjelmen et al 2019). The wealth of information available for this genus allows researchers to develop very ambitious large scale evolutionary studies with relative ease.…”
mentioning
confidence: 99%
See 1 more Smart Citation